MANPOWER SYSTEMS ANALYSIS AS A CORRELATE OF ORGANISATIONAL/MANAGEMENT EFFECTIVENESS IN SELECTED INDUSTRIES IN NIGERIA (1995)
This study examined manpower systems analysis as a correlate of Organisational/Management effectiveness in randomly selected industries in Nigeria with a view to finding out the relationship between the ability to survive of a business concern and the efficiency with which it utilises its human resources. The descriptive survey research design was employed for this research which covered service, manufacturing, transport, banking and petro-chemical industries. A total of 1,000 workers were randomly selected as subjects for this study. A questionnaire designed using a four-point Likert Scale and which comprised of the Industrial Staffers Job / commitment Questionnaire (I.S.C.Q.), Job Placement Questionnaire (J.P.Q.), structured interview on employment, training, job performance/ advancement, recruitment, and promotion, were used as the instrument for this study. Seven null hypotheses were postulated and tasted. The data collected were analysed using a set of statistical tools like the chi-square (X), Pearson Product Moment Correlation (r) at 0.05 level of confidence, t-test statistic, and analysis of Variance (ANOVA). The study established the following: (1) There was a significant correlation between manpower systems analysis and workers' morale in industry. (2) There was a significant correlation between manpower systems analysis and rate of absenteeism in industry. (3) There was a significant relationship between career development and workers' attitudes to their organisations. (4) There was a significant correlation between effective job placement and workers' productivity. (5) Manpower systems analysis significantly affects the market rate of return on capital assets. (6) There was a significant difference between the earnings per share resulting from fulfillment of workers' aspiration with respect to promotions and their non-fulfillment on entering the organisation. (7) There was a significant correlation between matching workers' systems analysis as a "sine qua non" for organisational/management effectiveness and therefore recommended that: (1) Employers of labour should engage in serious manpower system analysis so as to get and put the right number and kinds of people at the right places at the right time. (2) Employers should provide those working conditions that employees believe are necessary in order to secure and maintain their commitment to the organisation. (3) Workers should be assigned to jobs for which their aptitudes and abilities are well suited so as to reduce rate of absenteeism and increase their productivity in industry. (4) Organisations should develop interest in drawing up manpower systems analysis as an effective means of improving employees' job attitudes, behaviours and performance. Other recommendations and suggestions based on the findings of this study were also included.